2019
DOI: 10.1103/physrevx.9.041054
|View full text |Cite
|
Sign up to set email alerts
|

Linker-Mediated Phase Behavior of DNA-Coated Colloids

Abstract: The possibility of prescribing local interactions between nano-and microscopic components that direct them to assemble in a predictable fashion is a central goal of nanotechnology research. In this article we advance a new paradigm in which self-assembly of DNA-functionalized colloidal particles is programmed using linker oligonucleotides dispersed in solution. We find a phase diagram that is surprisingly rich compared to phase diagrams typical of other DNA-functionalized colloidal particles that interact by d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 44 publications
4
30
0
Order By: Relevance
“…8 actually accounts for multiparticle systems, which already includes multibody effects. Similar re-entrant melting was also found in a recent work of linkermediated immobile DNACCs, in which the ssDNA receptors are grafted on the colloids instead of being mobile on the particle surface (31). A local chemical equilibrium approach was used in (31) to treat the linker-mediated interaction between colloids, and it is related to the statistical mechanical description used here (24).…”
Section: Numerical Verification Of the Mean-field Theorysupporting
confidence: 62%
“…8 actually accounts for multiparticle systems, which already includes multibody effects. Similar re-entrant melting was also found in a recent work of linkermediated immobile DNACCs, in which the ssDNA receptors are grafted on the colloids instead of being mobile on the particle surface (31). A local chemical equilibrium approach was used in (31) to treat the linker-mediated interaction between colloids, and it is related to the statistical mechanical description used here (24).…”
Section: Numerical Verification Of the Mean-field Theorysupporting
confidence: 62%
“…1b is somehow analogous to the resolubilization of virus crystals [18], proteins [19], or nucleic acids [20] at a concentration of multivalent ions (forming inter-molecular bridges) higher than some mMs. Similarly, aggregates of ligandpresenting colloids cross-linked by short DNA oligomers dispersed in solution melt when increasing the concentration of the bridging molecule beyond a threshold value (ranging between 10 −8 M and 10 −4 M) which depends on the number of ligands per particle [21]. The proposed method, along with other simulation strategies implementing reaction moves in systems of multivalent chains [22][23][24][25][26][27][28][29][30], are ideal for studying the unfolding transition given that the high free energy barriers between competing states are sidestepped by dedicated MC moves.…”
Section: Introductionmentioning
confidence: 99%
“…For example, they found that the phase behavior of DNA-coated colloids can be altered by adding free DNA strands for displacement reaction, as mentioned above [62]. Then, using free DNA strands as the linkers to bridge grafted DNA on colloids' surface, they reported a reentrant melting transition upon increasing concentration of linker as well as the possibility to encode multiple interactions spontaneously [63]. In addition, colloidal crystals are constructed using free linker DNA, depending on the concentration and the symmetry of the linker.…”
Section: Crystallization Of Dna-coated Colloidsmentioning
confidence: 95%
“…Rogers et al [62][63][64][65][66] further investigated the physical behavior of the assembly of DNA-coated colloids mediated by free DNA strands. They argued that encoding information into the sequence and concentration of the free strands instead of the grafted strands could overcome the problems conventional colloidal self-assembly suffers, including uncollaborative mutual interactions and a limited number of interactions.…”
Section: Crystallization Of Dna-coated Colloidsmentioning
confidence: 99%